A Comprehensive Review on Biological Activity of Green Tea (Camellia sinensis) - Mansoori, Ruksar; Jain, Deepti; Pandey, Varsha; Jain, Surendra Kumar (Journal of Drug Delivery and Therapeutics, 2022)
Green tea, the commonly consumed beverage, is gaining increased attention in promoting overall health. In specific, green tea is considered a healthful beverage due to the biological activity of its polyphenols namely catechins. The main green tea polyphenols are catechins: (±)-catechin C, (-)-epicatechin EC, (+)-gallocatechin GC, (-)-epigallocatechin EGC, (-)-epicatechin gallate ECG, and (-)-epigallocatechin gallate EGCG. Among the polyphenols Epigallocatechin 3 gallate and Epicatechin 3 Gallate are the most predominant catechins. There are also human studies on using green tea catechins to treat chronic diseases such as obesity, type II diabetes, and cardiovascular risk factors. Long-term consumption of tea catechins could be beneficial against high-fat diet-induced obesity and type II diabetes and could reduce the risk of coronary disease. Several epidemiological studies have proved that green tea also has some general health benefitting properties like anti-obesitive agent, anti-oxidant, anti-aging, anti-diabetic, anti-hyperlipidemic, anti-hypertension, anti-cancer, anti-bacterial, anti-viral, anti-inflammatory, anti-parkinson's effects, anti-alzheimer's effects, anti-arthritic, anticollagenase, and antimutagenic etc. The properties of these catechins proved to be helpful in the treatment of chronic diseases like obesity, aging, diabetes, cardiovascular disease, hyperlipidemic, hypertension, cancer, microbial, parkinson's, alzheimer's, arthritis, and periodontal disease. There are numerous studies in humans, animal models, and cell lines which provide the concepts for underlying functional mechanisms of green tea catechins and their biological actions and to suggest potential health benefits from the consumption of tea, including prevention of cancer and heart diseases. The review highlights also the potentials of green tea, its health benefits in terms of their properties. The present review concentrates on the effects of green tea on different chronic disease and general health.Keywords: Green tea, Polyphenols, Epidemiological, Catechins, Animal models